Pyrolysis of microalgae residues – A kinetic study. (January 2016) - Bui, Hau-Huu; Tran, Khanh-Quang; Chen, Wei-Hsin
Highlights: Non-isothermal pyrolysis of microalgae residues. First parallel-model employed for kinetic modelling of microalgae pyrolysis. Five pseudo-components model was applied for kinetic modelling. Protein and lipid were included in the model. The simulation was successful to reflect the kinetic of pyrolysis process. Abstract: Pyrolysis of residues from the oil extraction process of two types of microalgae, Chlamydomonas ( C. sp. JSC4 ) and Chlorella sorokiniana ( C. Sorokiniana CY1 ) was studied by means of a thermogravimetric analyzer. Five pseudo-components (hemicellulose, cellulose, lignin, lipid and protein) model with n = 1 or n # 1 was assumed for a kinetic analysis of the collected pyrolysis data. The model with n # 1 resulted in a slightly better fit quality and reasonable kinetic parameters. The calculated activation energy of hemicellulose, cellulose, lignin, lipid, protein was 115.12–117.12 kJ/mol, 181.67–198.30 kJ/mol, 61.74–62.75 kJ/mol, 104.93–114.14 kJ/mol and 90.75–99.31 kJ/mol, respectively, for C. sp. JSC4 ; and 113.12–117.12 kJ/mol, 218.73–28.79 kJ/mol, 64.77–66.39 kJ/mol, 131.97–143.63 kJ/mol and 108.03–118.13 kJ/mol, respectively, for C. Sorokiniana CY1 .